A family of DNA aptamers with varied duplex region length that forms complexes with thrombin and prothrombin. Issue 16 (2nd July 2015) - Spiridonova, V.A.; Barinova, K.V.; Glinkina, K.A.; Melnichuk, A.V.; Gainutdynov, A.A.; Safenkova, I.V.; Dzantiev, B.B.
Abstract : Structural properties determine binding affinities of DNA aptamers specific to thrombin. Our paper is the first to focus on a family of eight G‐quadruplex‐based aptamers with varied duplex region length (from two to eight base pairs). We have shown that the duplex, which is not the main binding domain, greatly influences the interaction with thrombin and prothrombin. Furthermore, the affinity of an aptamer to thrombin and prothrombin increases (respectively from 2.7 × 10 −8 M to 5.6 × 10 −10 M and from 1.8 × 10 −5 M to 7.1 × 10 −9 M) with an increase in the number of nucleotide pairs in the duplex region. Abstract : We identified a family of eight G‐quadruplex‐based DNA aptamers specific to thrombin. Aptamers vary based on duplex region length (from two to eight base pairs). Duplex region length influences kinetic and equilibrium constants. Increasing duplex region length increases affinity to thrombin and prothrombin. The duplex, which is not the main binding domain, greatly influences the interaction.